ANALISIS MUATAN NILAI KARAKTER DISIPLIN PADA FILM ANIME MIMI O SUMASEBA - Nabilah, Karla Zulfa; Hidayat, Muhamad Taufik (STIT AL MULTAZAM, 2023)
Discipline is a character trait that must be instilled from an early age, as it can help a person achieve their goals. This study aimed to analyze and describe the character values of discipline in the anime film